5/6 nephrectomy using sharp bipolectomy via midline laparotomy in rats: method article - Studier-Fischer, Alexander; Özdemir, Berkin; Haney, Caelán Max; Egen, Luisa; Michel, Maurice Stephan; Westhoff, Niklas Christian; Mieth, Markus; Czigány, Zoltán; Salg, Gabriel Alexander; Nienhüser, Henrik; Billmann, Franck; Kowalewski, Karl-Friedrich (JoVE. Video journal, 2025)
Chronic kidney disease (CKD) affects over 10% of the global population, amounting to more than 800 million individuals worldwide. The advances in the treatment of CKD have had a significant impact on patient outcomes. While in the past, CKD was often considered a death sentence, with many patients succumbing to the complications of end-stage renal disease, it is now increasingly being managed as a chronic condition with the availability of dialysis and kidney transplantation, as well as new pharmaceutical developments such as SGLT2 inhibitors or nonsteroidal mineralocorticoid receptor antagonists. Yet, there continues to be a growing demand for further exploration into the pathophysiological processes and potential therapeutic interventions. Reliable biological models play a crucial role in facilitating this research. Given the multifaceted nature of renal disease, which encompasses not only cell biology but also vascular microanatomy and endocrine signaling, an appropriate model must possess a level of biological complexity that only an animal model can offer, rendering rodents an obvious choice. This manuscript, therefore, provides an intricate, systematic protocol for surgically reducing renal parenchyma through midline laparotomy and combined total and partial nephrectomy in rats for survival as well as non-survival applications. It emphasizes the critical role of precise surgical techniques in ensuring consistent and reliable outcomes. Prime examples of potential applications for this model include biomolecular and pharmaceutical studies as well as the development of innovative intraoperative imaging modalities, such as hyperspectral imaging, to objectively visualize and differentiate renal malperfusion.
Gesehen am 30.06.2025
Wissenschaftlicher Film. Deutschland. 2025
Keywords: Film